Analisis Tingkat Kepuasan Pengguna Aplikasi Alfagift Menggunakan Metode End User Computing Satisfaction Dan Net Promoter Score - Wahyu Ningrat; Syahriani, Syahriani (Antartika Media Indonesia, 2025)
This study aims to measure the level of user satisfaction and loyalty of the Alfagift application using the End User Computing Satisfaction (EUCS) and Net Promoter Score (NPS) methods, and to test the relationship between the two. Data was collected from 105 respondents through questionnaires and analyzed using a quantitative approach. The satisfaction score (RK) for each EUCS dimension was calculated using the formula based on Kaplan and Norton's definition. The results show that all dimensions fall under the “Satisfied” category: Content (4.17), Accuracy (4.12), Format (4.26), Ease of Use (4.25), Timeliness (4.09), and Satisfaction (4.28). Regression analysis reveals that three dimensions (Ease of Use, Content, and Format) have a significant partial effect on user satisfaction, while all dimensions collectively have a significant effect. The Net Promoter Score (NPS) obtained is 42.86%, categorized as positive (promoter), indicating that most users are loyal and willing to recommend the Alfagift application. Multiple linear regression testing also shows that user satisfaction significantly affects user loyalty.